RELATIONSHIP BETWEEN COMPLIANCE IN TAKING MEDICATION AND THE INCIDENCE OF HYPERTENSION COMPLICATIONS AT RSAU dr. EFRAM HARSANA LANUD ISWAHJUDI - Muhammadin, Lutfi Nur; Nurhidayat, Saiful; Putri, Dianita; Isro’in, Laily; Andarmoyo, Sulistyo (The SDGS Forum Communication, 2025)
One non-communicable disease that plagues the health sector, particularly in hospitals, is hypertension. The goal of treatment for hypertension patients is to improve the quality of life, so patient compliance is needed for those who are undergoing hypertension treatment in order to obtain a better quality of life for patients and avoid complications of the disease. This study was conducted to determine compliance with taking medication with the incidence of hypertension complications. This research method uses descriptive correlation with a cross-sectional approach to 93 respondents at RSAU Dr. Efram Harsana with purposive sampling using the MMAS questionnaire. The data analysis will be used is the chi-square correlation statistical test. For the results, if the ρ value ≥ 0.05, then H0 is accepted, and if the ρ value ≤ 0.05, then Ha is accepted. For the results, if the ρ value ≥ 0.05, then H0 is accepted, and if the ρ value ≤ 0.05, then Ha is accepted. The results of the study showed that the majority of respondents had compliance with taking medication in the moderate category, as many as 50 people (53.8%); high compliance, as many as 26 people (28.0%); and low compliance, as many as 17 people (18.3%). The majority of respondents in this study were female, as many as 57 people (61.3%), and male respondents were as many as 36 people (38.7%). The data were processed and analyzed using the chi-square test with α = 0.05. The results of the study obtained a moderate level of compliance of 53.8% of 93 respondents. Based on statistical tests, it is known that a P-value of 0.000 < 0.05 indicates that H1 is accepted, which means that there is a relationship between medication compliance and the study of hypertension complications. From the research above, respondents are expected to be able to understand the importance of being obedient in taking medication so that they can prevent complications from hypertension in the future